Ludmila Ulickaja’s play Russian Preserves: Capturing the view of reality with the help of the classics - Olaszek, Barbara (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2011)
The main focus of this essay is creative ways of depicting contemporary Russian reality in Ludmila Ulickaja’s play Russian Preserves. The image of reality is created on the basis of quotations, topical references and reminiscences from classical literature, books of history and popular culture. The assessment of reality is made through clue words, sublime words, witticisms and paradoxes, usually used with a hint of irony. The inclusion of the interlude with its parody function contributes to the ideological meaning: the contemporary Russia is on the verge of catastrophe.